(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
This article aims to describe the implementation of customary criminal sanctions used by the Baduy community in maintaining and preserving their nature and the effectiveness of the use of customary sanctions in preventing and overcoming actions that damage the environment of the Baduy community. It is a qualitative research to produce descriptive data, where the approach used is socio-legal research using secondary data as a normative or doctrinal approach, and uses a social approach to explore primary data in the form of values and interpret the behavior of local communities in solving customary cases. The results of this study indicate that the life of the Baduy community which is supported by agriculture and cultivation is very dependent on natural preservation. The maintenance and preservation of the environment in the Baduy community is highly respected. Various ways to preserve nature through avoidance of goods and modern lifestyle are carried out from generation to generation so as not to change the order of nature and the environment. In preserving nature, the Baduy community provides guidelines on certain actions that their indigenous people should not take, such as burning forests, cutting trees in certain areas.